The sales success handbook : - Richardson, Linda (McGraw-Hill, 2006)
To sell today, salespeople must add value, provide perspective, and show customers how a product will solve their specific needs. The Sales Success Handbook outlines a six-step program for hearing and understanding exactly what customers have to say and for selling solutions--instead of just selling products.